PENGARUH IMPLEMENTASI BAURAN PEMASARAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA PIZZA HUT RESTAURANT METROPOLITAN CITY PANAM PEKANBARU - Sari, Annisa Dewita; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Purchasing decisions are an important part of the product marketing concept, this is the background of this research. Implementing the right marketing mix and a good brand image in front of consumers are part of the factors supporting consumer purchasing decisions. This strategy is applied by Pizza Hut Restaurant Metropolitan City Panam Pekanbaru. This study aims to determine the effect of Marketing Mix Implementation and Brand Image on purchasing decisions at Pizza Hut Restaurant Metropolitan City Panam Pekanbaru. The method used in this research is descriptive and quantitative, with the source of the data from this study coming from primary data obtained through the interview process and distributing questionnaires which were then tested statistically through the SPSS program and secondary data using product sales data for Pizza Hut Restaurant Metropolitan City Panam from 2016-2020. The analytical method used in this research is simple and multiple regression analysis, and through validity and reliability tests. In this study the results obtained are that the Marketing Mix (X1) has a positive and significant effect on Purchase Decisions (Y), Brand Image (X2) has a positive and significant effect on Purchase Decisions (Y),Keywords: Marketing Mix, Brand Image and Purchase Decision